A Comprehensive Structural and Functional Analysis of Saccharomyces Killer Toxins - Creagh, Jack W.; Reetz, David C.; Givens, Lily L.; Coss, Sarah A.; Bizarria, Rodolfo [UNESP]; Patel, Jagdish Suresh; Rodrigues, Andre [UNESP]; Ytreberg, F. Marty; Rowley, Paul A. (Cold Spring Harbor Laboratory, 2025)
Antifungal killer toxins are cytotoxic proteins that have the potential to combat the growing threat of fungi to human health and agriculture. A lack of empirical tertiary structures has placed limitations on understanding their mechanisms of action and targeting of pathogens. AlphaFold and molecular dynamics simulations were used to create tertiary structure models of all canonical Saccharomyces killer toxins. These models have enabled the prediction of the functional domains of killer toxins and postranslational modifications, including sites of proteolytic cleavage and disulfide bonds. They have also revealed unexpected homology between Saccharomyces killer toxins, suggesting that all but K28 are likely ionophores. Structural homology with the well-studied killer toxins K1 and K2 enabled prior empirical data to predict the antifungal and immunity mechanisms of the K1L, K21, K45, K74, and KHS toxins. The understudied killer toxins Klus, KHR, and K62 were found to have homology to bacterial and plant toxins, including members of the aerolysin family and antifungal lectins. These structural similarities provided clues for the mechanisms of killer toxin carbohydrate binding, oligomerization, and membrane attack. Given the hundreds of sequence homologs of the Saccharomyces killer toxin identified across fungi, modeling studies offer an exciting opportunity to characterize novel toxin-like proteins. This approach is strengthened by the continued use of the model yeast S. cerevisiae to study killer toxins and the wealth of functional data gathered in the decades since their first discovery.